Estudio de factibilidad para la creación de una empresa consultora de servicios empresariales para los socios de la cámara de comercio del Cantón La Maná, provincia de Cotopaxi, año 2008 - Minda Lastra, Gladys Maribel (2011)
The service of consultancy is an activity aimed to all entities, since it allows starting from an analysis of the information flow to diagnose, identify and define the main problems of the organization. That is why this consultancy service is taken as the beginning for the solution of the problems that were identified in the Commerce Association members’ companies. In the field study was determined that the members’ companies do not count on any kind of consultancy because of the ignorance of the scientific methods; this is the reason which a study of feasibility for the creation of a business services consultancy company is proposed.